Challenges, Skills and Roles for Information Professionals in Managing Big Data - Adlina Khamis, Nur; Farik Mat Yatin, Saiful; Nabilah Maidin, Farah; Mat Rashid, Rasmira; Akmar Ismail, Saidatul; Saifuddin, Norshila; Kamis, Yamin (International Journal of Engineering and Technology, 2018)
Big data is a now well used term designed to define the growing volume, variety, velocity, variability and value of information surging through organizations. The benefits that can be utilize from big data will only come about if the information is resourceful and been managed properly. As the amount and variety of data grows, so do the skills required to capture, manage, and analyze the data. The investigation for associations is making sense of how to get from existing data and application frameworks to flawlessly ingesting any key information sorts from all sources and quickly displaying bits of knowledge to chiefs. This article discusses about big data challenges faced by information professionals, the skills needs and roles for them in managing it.Â Â